Alchemical Rubedo in Jill Mellick's "The Red Book Hours": Ecosophy on the Spirit - Antonella Riem (Interdisciplinary Journal of Partnership Studies, 2020)
According to the biocultural partnership-dominator lens as expounded by Riane Eisler, this article studies the echoes and analogies between the opus alchymicum and the instruments of self-growth and transformation found in Jung’s The Red Book and Jill Mellick’s profound, insightful and exquisite The Red Book Hours. Eisler’s method is significantly interrelational and systemic, it supersedes traditional binary oppositions and offers an interesting correlation with alchemy. Mellick’s monumental The Red Book Hours is not only a profound scholarly study of Jung’s own extraordinary Red Book, but also a multifaceted, dynamic and living work which sheds light on the process of Self-analysis as a breakthrough towards wholeness.